2021
DOI: 10.3390/ijerph18041618
|View full text |Cite
|
Sign up to set email alerts
|

Building a Prevention System: Infrastructure to Strengthen Health Promotion Outcomes

Abstract: Prevention systems improve the performance of health promotion interventions. This research describes the establishment of the Australian state government initiative, Healthy Together Victoria’s (HTV) macro infrastructure for the delivery of large-scale prevention interventions. Methods: This paper reports on findings of 31 semi-structured interviews about participants’ understanding of systems thinking and their reflections of the strengths and weaknesses of the HTV prevention system. A chronic disease preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 57 publications
(95 reference statements)
0
44
0
Order By: Relevance
“…In terms of research aims found in the 23 articles, four themes emerged: 1) to examine the complexity of a public health topic and illustrate complex systems thinking [26][27][28][29][30][31][32][33][34]; 2) to discuss the complexity of a public health intervention [35][36][37][38][39][40]; 3) to describe study protocol and how CLDs were created [41][42][43][44]; and 4) to illustrate how CLDs can be used to monitor and track initiatives to improve population health or evaluate impact of interventions [45][46][47][48].…”
Section: Research Aimsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of research aims found in the 23 articles, four themes emerged: 1) to examine the complexity of a public health topic and illustrate complex systems thinking [26][27][28][29][30][31][32][33][34]; 2) to discuss the complexity of a public health intervention [35][36][37][38][39][40]; 3) to describe study protocol and how CLDs were created [41][42][43][44]; and 4) to illustrate how CLDs can be used to monitor and track initiatives to improve population health or evaluate impact of interventions [45][46][47][48].…”
Section: Research Aimsmentioning
confidence: 99%
“…Both primary and secondary data were used for creating CLDs (Table 3). Most articles reported on primary data collection (18/ 23) and this included interviews [26,27,33,[35][36][37][38][39][40], group model building with stakeholders and/or community members [32,41,43,44,46,48], behavioral data [42,47], fieldnotes [37], and workshops with experts [31]. Twelve articles used primary data only.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, the appointment of personnel without appropriate training in public health or health promotion, the prevalence of small teams dedicated to prevention, and staff turnover due to lack of role clarity and/or funding stability, has been found to significantly impair the quality and continuity of prevention programs in Australia. 9,10 This highlights the need for public health agencies to review criteria for staff selection, the size and structure of teams, duration of appointments, remuneration, training and opportunities for career advancement, which will affect the composition and continuity of the prevention workforce at the regional level.…”
Section: Regional Workforce Capacitymentioning
confidence: 99%
“…Systems thinking can determine the relationships between actors (e.g. individuals or organisations), facilitating discussions which can lead to a better understanding of the shifting influences that exist and affect a network's operation (Bensberg, Joyce, & Wilson, 2021;Carey et al, 2015). A network's structure can be explored using social network analysis (SNA), which can assist in developing an understanding of the opportunities and constraints placed on individuals and organisations and the roles they play in the outcomes of the network (Borgatti, Everett, & Johnson, 2018;Valente, 2010).…”
Section: Introductionmentioning
confidence: 99%